2021
DOI: 10.3389/fphar.2021.736511
|View full text |Cite
|
Sign up to set email alerts
|

Targeting of Protein’s Messenger RNA for Viral Replication, Assembly and Release in SARS-CoV-2 Using Whole Genomic Data From South Africa: Therapeutic Potentials of Cannabis Sativa L

Abstract: The possible evolutionary trend of COVID-19 in South Africa was investigated by comparing the genome of SARS-CoV-2 isolated from a patient in KwaZulu-Natal, South Africa with those isolated from China, Spain, Italy, and United States, as well as the genomes of Bat SARS CoV, Middle East Respiratory Syndrome Coronavirus (MERS-CoV), Mouse Hepatitis Virus (MHV), and Infectious Bronchitis Virus (IBV). Phylogenetic analysis revealed a strong homology (96%) between the genomes of SARS-CoV-2 isolated from KwaZulu-Nata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…The summary of evidence suggesting that CBG may represent a lead antimicrobial cannabinoid is illuminating [ 12 ]. Further, there is a pressing interest in the potential of cannabinoids, such as CBD, to inhibit SARS-CoV-2 cellular entry and replication through varying mechanisms [ 48 , 49 , 101 ]. This review augments these prior articles by focusing on the most recent literature on cannabis-related antimicrobials, primarily summarized in Table 1 , Table 2 , Table 3 , Table 4 and Table 5 , and providing a synopsis of the knowledge gaps that act as a barrier to the acceptance and utility of cannabinoid-based antimicrobial therapeutics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The summary of evidence suggesting that CBG may represent a lead antimicrobial cannabinoid is illuminating [ 12 ]. Further, there is a pressing interest in the potential of cannabinoids, such as CBD, to inhibit SARS-CoV-2 cellular entry and replication through varying mechanisms [ 48 , 49 , 101 ]. This review augments these prior articles by focusing on the most recent literature on cannabis-related antimicrobials, primarily summarized in Table 1 , Table 2 , Table 3 , Table 4 and Table 5 , and providing a synopsis of the knowledge gaps that act as a barrier to the acceptance and utility of cannabinoid-based antimicrobial therapeutics.…”
Section: Discussionmentioning
confidence: 99%
“…CB1 and CB2, at least at the mRNA level, are upregulated in circulating immune cells in individuals with moderate to severe disease [ 100 ]. One report found that several cannabinoids, including tetrahydrocannabivarin (THCV), THC, CBG, and CBN, are computationally predicted to interact with mRNAs encoding proteins assumed to be involved in SARS-CoV-2 replication, translation, assembly and release (ORF1ab, surface glycoprotein, envelope protein, nucleocapsid phosphoprotein) [ 101 ], although effective inhibition of such a broad range of translational events has yet to be confirmed in vitro or in vivo. Altyar et al screened, in silico, 45 cannabinoids for their potential to interact with key SARS-CoV-2 enzymes, noting that cannabichromanon (CBCN) was best suited as a potential inhibitor of MPro and Plpro [ 102 ].…”
Section: Translational Considerations For the Development Of Cannabis...mentioning
confidence: 99%
“…Erukainure et al. ( 2021 ) studied the phytochemical constituents of Cannabis sativa L. (Cannabaceae). Through MD, it was found that cannabinol, tetrahydrocannabivarin, tetrahydrocannabinol, cannabispiran, cannabidiol, and cannabigerol have binding affinities ranging from −40.78 to −36.21 kcal −1 for the nucleocapsid phosphoprotein translation initiation site and nucleocapsid phosphoprotein translation termination site.…”
Section: Assembly and Release Inhibitors Against Sars-cov-2mentioning
confidence: 99%
“…Natural compounds are promising targets for drug development, and a number of therapies have been inspired and based on natural products [21]. Molecular docking analysis revealed strong binding affinities between the phytocannabinoids and codon mRNAs of proteins implicated in replication, translation and release of SARS-CoV-2, which portrays cannabinoids as potential drugs against COVID-19 [22]. Moreover, inhibition of the main protease among coronaviruses-M pro , which plays a significant role in the COVID-19 virus replication process-is also considered a potential therapeutic target [23,24].…”
Section: Antiviral Properties Of Cannabinoidsmentioning
confidence: 99%